Performance of Convection Employees Facing Society : HR Development, Muslim Coworkers Support , and Spiritual Motivation - Yuliani, Isna Dewi; Aflah, Kuntarno Noor; Jalil, Abdul (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
The research objective was to determine the effect of employee performance in facing the era of society in terms of human resource development, Muslim coworkers support, and spiritual motivation in the Kudus Convection UMKM, both positively and significantly. This research method uses field research with a quantitative approach and is analyzed using SmartPLS 3. The population is convection SMEs in Kudus, and the sample is 125 respondents. The analysis results of validity and reliability tests are valid and reliable. The results of this study indicate that HR development has a positive and significant effect on employee performance, Muslim coworkers support has a positive and significant impact on employee performance, and spiritual motivation has a positive and significant effect on employee performance. This research contributes to aligning modern management principles and the latest trends in the business world and preparing human resources to face the demands of the convection industry, which is growing. Recommendations for further research are that it can broaden the sampling not only in one city, can apply Islamic values more in the context of work, and can add other factors that have not been studied in this study.